PSVI-40 Anthelmintic Resistance Testing on Sheep Farms. - Whitley, N (J Anim Sci, 2018)
A collaborative project was conducted to determine the status of gastrointestinal nematode (GIN) parasite anthelmintic resistance on commercial sheep farms in Georgia (GA), Maryland (MD), and Virginia (VA), USA (n=10/state), with support from the American Sheep Industry Association. Pooled fecal samples were collected for a fecal egg count (FEC), larval identification and DrenchRite® larval development assay (LDA) for each farm. The LDA critical well values were used to determine farm GIN drug resistance status as associated with FEC reduction percentages for levamisole, fenbendazole, ivermectin, and moxidectin (resistance=less than 95% reduction). Percentage and FEC data were log transformed for analysis/inferences but LSMEANS reported. The most commonly identified parasite larvae was Haemonchus contortus(83.9, 89.4, and 73.3%, for GA, MD, and VA, SEM=3.1%; GA=MD>VA, P < 0.02). Average FEC was 3694, 5080 and 3014 (SEM=487) eggs per gram of feces for GA, MD and VA, respectively, with VA exhibiting the lowest FEC (P<0.05) but GA similar to MD. Resistance to moxidectin and levamisole was lower on MD compared to VA and GA farms (P<0.04). All farms had resistance to fenbendazole, and ivermectin resistance was similar among states, averaging 100, 80 and 100% (SEM=9.4%) for GA, MD and VA, respectively. For multiple drug resistance, 100% of GA and VA farms had resistance to at least three drugs (MD lower at 80% for two drugs, SEM=3.8% and 60% for three drugs, SEM=4.7%; P<0.001). In addition, the percentage of farms with resistance to all tested drugs was 40, 0 and 60% for GA, MD and VA; all different, P<0.04; SEM=6.7%). In summary, all farms had resistance to one or more anthelmintics, but there were differences between farms and states. This data underlines the critical importance of understanding anthelmintic resistance and implementing parasite management practices to slow the rate of resistance on farms.